Lagi na lamang ba akong babae? - Bernal, Ishmael; Nardes,Orlando (Regal Films, 1978)
A lovely rural girl went to Manila to look for greener pastures. He worked as a restaurant waitress and a night club dancer. She was a mistress to three rich men. In the end, she was reunited with his childhood boyfriend.